2019
DOI: 10.1177/2058738419827745
|View full text |Cite
|
Sign up to set email alerts
|

Reuterinos® as adjuvant for peri-implant treatment: A pilot study

Abstract: The objective of this study was to evaluate the effects of lozenges-containing Lactobacillus reuteri as an adjuvant treatment of peri-implant mucositis and to detect the level of L. reuteri colonization in the peri-implant tissues of treated patients. A total of 10 patients were selected. Subjects with at least one implant affected by peri-implant mucositis, with gingival index (GI) of ⩾2 in each quadrant, evaluated at the buccal aspect of all teeth. Patients included in the study were partially edentulous and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 6 publications
2
24
0
Order By: Relevance
“…There were no clinical and microbiological benefits from the administration of the probiotics. Similar negative results were obtained by Lauritano et al [63], who evaluated the daily consumption of L. reuteri tablets for 28 days in patients with peri-implant mucositis, by Peña et al [64] who studied the addition for 1 month of L. reuteri DSM 17938 and ATCC PTA in patients with peri-implant mucositis who received mechanical therapy and 0.12% chlorhexidine 15 days before the start of probiotic intervention, by Galofré et al [65] who also evaluated the effects of administration of L. reuteri DSM 17938 and ATCC PTA 5289 in patients with peri-implant mucositis and peri-implantitis for 30 days, and by Hallström et al [29] who administered L. reuteri DSM 17938 and ATCC PTA 5289 in patients with peri-implant mucositis for 3 months. Mongardini et al [66] also found no clinical benefits after 14-days administration of L. plantarum and L. brevis on patients with experimental peri-implant mucositis.…”
Section: Probiotics In Peri-implant Diseasessupporting
confidence: 91%
“…There were no clinical and microbiological benefits from the administration of the probiotics. Similar negative results were obtained by Lauritano et al [63], who evaluated the daily consumption of L. reuteri tablets for 28 days in patients with peri-implant mucositis, by Peña et al [64] who studied the addition for 1 month of L. reuteri DSM 17938 and ATCC PTA in patients with peri-implant mucositis who received mechanical therapy and 0.12% chlorhexidine 15 days before the start of probiotic intervention, by Galofré et al [65] who also evaluated the effects of administration of L. reuteri DSM 17938 and ATCC PTA 5289 in patients with peri-implant mucositis and peri-implantitis for 30 days, and by Hallström et al [29] who administered L. reuteri DSM 17938 and ATCC PTA 5289 in patients with peri-implant mucositis for 3 months. Mongardini et al [66] also found no clinical benefits after 14-days administration of L. plantarum and L. brevis on patients with experimental peri-implant mucositis.…”
Section: Probiotics In Peri-implant Diseasessupporting
confidence: 91%
“…After the removal of duplicates, 199 remained. Eighteen full-text articles were assessed, and ultimately, 7 ( Flichy-Fernández et al., 2015 ; Hallström et al., 2016 ; Galofré et al., 2018 ; Tada et al., 2018 ; Lauritano et al., 2019 ; Peña et al., 2019 ; Laleman et al., 2020 ) papers were included in the qualitative synthesis and 4 in the meta-analysis synthesis ( Flichy-Fernández et al., 2015 ; Galofré et al., 2018 ; Peña et al., 2019 ; Laleman et al., 2020 ), as illustrated in Figure 1B .…”
Section: Resultsmentioning
confidence: 99%
“…The study characteristics are summarized in Table 2 . Seven intervention studies investigating the effects from probiotic supplements to the non-surgical treatment of peri-implant mucositis and peri-implantitis were included ( Flichy-Fernández et al., 2015 ; Hallström et al., 2016 ; Galofré et al., 2018 ; Tada et al., 2018 ; Lauritano et al., 2019 ; Peña et al., 2019 ; Laleman et al., 2020 ). All studies were placebo-controlled, blinded, and randomized.…”
Section: Resultsmentioning
confidence: 99%
“…The reasons for excluding specific studies are summarized in Table 1 . One study reported probiotic therapy without nonsurgical mechanical therapy ( Flichy-Fernández et al, 2015 ), and one study lacked the data of clinical examination of the implant inflammation ( Lauritano et al, 2019 ). The other study was excluded because it was written in Russian ( Ahmedbeyli et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%